Synthesis of Tin Oxide Nanocrystallites with Various Calcination Temperatures Using Co-Precipitation Method with Local Tin Chloride Precursor - Panthoko, Norbert Egan Christo; Septiningrum, Fairuz; Yuwono, Akhmad Herman; Nurhidayah, Eka; Maulana, Fakhri Akbar; Sofyan, Nofrijon; Dhaneswara, Donanta; Lalasari, Latifa Hanum; Arini, Tri; Andriyah, Lia; Firdiyono, Florentinus; Ardianto, Yahya Winda; Pawan, Ria Wardhani (Metalurgi, 2023)
Indonesia is one of the largest tin metal producers in the world, and one of its derivative products is tin chloride (SnCl4). This material has been used as a raw ingredient for the production of organotin compounds such as methyltin mercaptide for PVC (polyvinyl chloride) plastic industry as a heat stabilizer. On the other hand, this precursor can be used to synthesize SnO2 nanomaterials, which have other strategic potentials, including photocatalysts and solar cell applications. In this study, the synthesis of SnO2 nanocrystallites was carried out using a local tin chloride precursor via the co-precipitation method, followed by a calcination process at temperatures of 300, 400, 500, and 600 °C, for further usage as an ETL (electron transport layer) in a PSC (perovskite solar cell) device. The basic properties characterization was carried out using XRD (X-ray diffraction), ultraviolet-visible (UV-Vis) spectroscopy, and SEM (scanning electron microscopy), while the photocurrent-voltage (I-V) curve photovoltaic performance of the device was performed using a semiconductor parameter analyzer. The characterization results showed that increasing the calcination temperature from 300 to 600 °C increased the average crystallite size from 1.19 to 13.75 nm and decreased the band gap energy from 3.57 to 3.10 eV. The highest PCE (power conversion efficiency) was obtained from the device fabricated with SnO2 nanocrystallites calcined at a temperature of 300 °C, which was 0.0024%. This result was obtained due to the highest transmittance of this sample as compared to others; the higher the transmittance, the better the performance of the ETL, which in turn increased the overall efficiency of the PSC